Corporate governance and real earnings management in Nigerian financial institutions: the moderating effect of independent directors - Abubakar, Ibrahim Adamu (2019)
The need for an improved quality of financial reports become a key challenge for investors and other stakeholders due to financial scandal being witnessed in Nigerian financial institutions. Related to that issue, this study examines whether corporate governance mechanisms (board and ownership structure) have an influence towards real earnings management (REM) practices in Nigerian financial institutions. In addition, the study also examines whether independent directors could moderate the relationship between board structure and ownership structure with REM in the Nigerian financial institutions. The unit of analysis of this study is 45 financial institutions listed in the Nigerian Stock Exchange for the period 2011 to 2016. Data of board structure (size, meeting frequency, board member expertise, female director, CEO tenure, CEO education level and CEO duality) and ownership structure (block ownership, foreign ownership, CEO ownership, and managerial ownership) are used to examine their relationship with REM. Using panel data, the multiple regression analysis is utilised to identify the relationship between corporate governance mechanisms with REM. The result displays a significant negative relationship between female directors and block ownership with REM. However, there is a significant positive relationship between board meeting, CEO education level, foreign ownership and independent directors with REM which might be due to insufficient information on the new REM technique within financial institutions in Nigerian. Meanwhile, independent directors significantly moderate the negative relationship between board meeting frequency, CEO education level and foreign ownership with REM. Nevertheless, the independent director's influence is found to be significant and positively moderate the relationship between female directors and block ownership with REM. The results have implication to regulators, investors, policy makers and other stakeholders, as the findings of this study recognise the important role played by both board and ownership structure in enhancing the quality of financial reports.